Verbal Behavior and Correspondence in the Film Rashomon - de Rose, Julio Cesar (Perspectivas em Análise do Comportamento, 2019)
Rashomon, the movie directed by Akira Kurosawa (1950), is virtually in all lists of best all time movies made by cinema connoisseurs. Several characters in the movie report the same event but the accounts are completely different. In this article we treat the characters as if they were real persons. Their reports are, therefore, treated as if they were real verbal behavior, controlled by real contingencies. We may ask, therefore, what variables were responsible for the discrepancies in the stories. In this case it is possible to raise plausible hypotheses, but a crucial element to evaluate such hypotheses is missing: we could know what happened only based on the report by the witnesses. As there is no independent confirmation of the story’s details, we cannot estimate to what extent the descriptions were indeed under control of the reported facts and to what extent they were controlled by variables that could distort the testimonies.